Digital Literacy Ability towards Curiosity Level and Student Self-Determination - Rini, Riswanti; Suryadinata, Nurain; Efendi, Ujang (Jurnal Pendidikan Progresif, 2022)
The purpose of this study was to analyze digital literacy skills on the level of curiosity and self-determination of students. This study uses a quantitative approach with statistical methods. The type of research used in this research is ex-post facto. The population in this study were students in Indonesia aged 17-22 years with a sample of 723 selected randomly. The instruments used are digital literacy measurement, the Curiosity measurement scale, and the self-determination measurement scale. Data analysis used statistical tests, namely the Mann-Whitney test and Simple Linear Regression. The main result of this research is that there are differences in digital literacy and self-determination in terms of gender, but in the aspect of Curiosity there is no difference. Furthermore, there is a positive effect of digital literacy on curiosity and self-determination. The digital literacy prediction model for Curiosity is Y=11.28+0.38X and the digital literacy prediction model for self-determination is Y=25.77+0.57X. Keywords: college student, curiosity, digital literacy, self-determination.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202224